2013
DOI: 10.2139/ssrn.2220720
|View full text |Cite
|
Sign up to set email alerts
|

The Non-Equivalence of Labor Market Taxes: A Real-Effort Experiment

Abstract: Under full rationality, a labor market tax levied on employers and a corresponding income tax levied on employees are equivalent. With boundedly rational agents, this equivalence is no longer obvious and the different reactions to these two taxes become important for policy making, political economics, and optimal taxation theory. In a real effort laboratory experiment, we study the differential effects of the two taxes on preferences concerning the size of the public sector, subjective well-being, labor suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Part 1 is the same in all sessions and is taken from Weber and Schram (2017). Participants are presented with a sequence of pairs of 10 9 10 matrices filled with two-digit numbers.…”
Section: Taskmentioning
confidence: 99%
“…Part 1 is the same in all sessions and is taken from Weber and Schram (2017). Participants are presented with a sequence of pairs of 10 9 10 matrices filled with two-digit numbers.…”
Section: Taskmentioning
confidence: 99%
“…5 Hayashi et al (2013) failed to find tax aversion in the binary decision of whether to accept a job in the laboratory; when subjects were shown net wages alongside gross wages, labor supply did not vary with tax structure. 6 To our knowledge, among the experimental literature within economics only Weber and Schram (2013) investigate statutory incidence -measuring subjects' effort when facing taxes imposed either on employees or on employers. In the experimental instructions used by Weber and Schram (2013), however, the word tax is never mentioned and the wage changes as workers provide effort, so the differences in productivity across treatments (observed among men but not women) appear to be due to their ability (or inability) to do the somewhat complicated math required to calculate the net wage.…”
Section: Experimental Designmentioning
confidence: 99%
“…6 To our knowledge, among the experimental literature within economics only Weber and Schram (2013) investigate statutory incidence -measuring subjects' effort when facing taxes imposed either on employees or on employers. In the experimental instructions used by Weber and Schram (2013), however, the word tax is never mentioned and the wage changes as workers provide effort, so the differences in productivity across treatments (observed among men but not women) appear to be due to their ability (or inability) to do the somewhat complicated math required to calculate the net wage. 7 The explanation presented in Lehmann et al (2013) centers on wage rigidity: that wages change less in response to employer side taxes as in Muysken et al (1999).…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…experiments by Weber and Schram (2013) and Kerschbamer and Kirchsteiger (2000) found that subjects have on average a higher after-tax pay-off, when their negotiation partners have to pay the tax. They propose that the legal burden of a tax might induce a moral obligation to bear it.…”
mentioning
confidence: 97%